Injury patterns in rural and urban Uganda - Kobusingye, O.; Guwatudde, D.; Lett, R. (Injury prevention, 2001)
To describe and contrast injury patterns in rural and urban Uganda. Settings—One rural and one urban community in Uganda. Methods—Community health workers interviewed adult respondents in households selected by multistage sampling, using a standardized questionnaire. Results—In the rural setting, 1673 households, with 7427 persons, were surveyed. Injuries had an annual mortality rate of 92/100 000 persons, and disabilities a prevalence proportion of 0.7%. In the urban setting 2322 households, with 10 982 people, were surveyed. Injuries had an annual mortality rate of 217/100 000, and injury disabilities a prevalence proportion of 2.8%. The total incidence of fatal, disabling, and recovered injuries was 116/1000/ year. Leading causes of death were drowning in the rural setting, and road traffic in the city. Conclusion—Injuries are a substantial burden in Uganda, withmuch higher rates than those in mostWestern countries. The urban population is at a higher risk than the rural population, and the patterns of injury differ. Interventions to control injuries should be a priority in Uganda.
Keywords: Injury patterns; Rural and urban Uganda